Reward and Punishment Effects on Error Processing and Conflict Control - Stürmer, Birgit (Frontiers in Psychology, 2011)
Recently, positive mood has been shown to reduce cognitive conflicts and adaptation related to conflict control. Van Steenbergen et al. (2009) proposed that short-term adaptation after conflict is driven by the aversive quality of the conflict. They reasoned that monetary gain and its positive emotional consequences might counteract the aversive quality of the preceding conflict and hence reduce subsequent conflict-driven adaptation processes. According to Ashby et al. (1999), however, positive affect increases cognitive flexibility and might, therefore, support cognitive conflict control. In two experiments, we combined Simon-type conflicts with monetary gains and losses in between trials and analyzed event-related brain potentials (ERPs). In Experiment 1 gains and losses were applied randomly as a lottery in between two Simon trials whereas in the second experiment gains and losses were related to behavioral performance. Either the 25 % fastest responses were rewarded or the 25 % slowest responses were penalized. In Experiment 1 conflict adaptation was not at all modulated by gains and losses and in Experiment 2 conflict adaptation increased after a gain. In addition we analyzed the error-related negativity (ERN) in Experiment 2 – a brain signal proposed to be related to the reward prediction error and response conflicts. The ERN and post-error slowing were enlarged in the context of reward. We conclude that a context of reward increases the subjective value of an error, thus, enhancing error adaptation. However, modulatory effects of affective states on cognitive conflict control are much more limited as previously asserted.